THE CORPORATE MUSEUMS AND THEIR SOCIAL FUNCTION: SOME EVIDENCE FROM ITALY - Mariacristina Bonti (European Scientific Journal, ESJ, 2014)
The Corporate Museum is a field of study that has been little explored and that occupies a particular position, at the intersection of the cultural realm of public museums and the world of business, and is characterized by a managerial vision. Corporate museums are physical structures in which the history and the memory of a company are told. The few works in this area look at these museums as a storehouse of organizational memory, as a tool for public relations and marketing, that is, for corporate communication. Although mainly framed in the context of corporate communication tools, studies conducted so far have neglected the potential of these structures as an expression of a social orientation of the firm, first demonstrated by attention to satisfying the legitimate expectations of the stakeholders (primarily, employees and local community). This paper intends to offer a contribution in this direction. We propose to strengthen studies that show a link between Corporate Museums and social oriented behaviors and to investigate the organizational conditions that could allow Corporate Museums to play a social role.